Analysis of surface water quality indicators in the Dnipro-Bug Estuary region in the first months after the destruction of the Kakhovka hydroelectric power station dam - Trokhymenko, Ganna; Magas, Natalia; Shumilova, Oleksandra; Klochko, Volodymyr (Видавництво Львівської політехніки, 2023)
The article presents the results of the analysis of surface water quality indicators changes in water bodies near settlements in the Mykolaiv region in the areas that were flooded after the destruction of the Kakhovka HPP. The analysis of critical water quality monitoring data on sanitary, chemical and microbiological indicators revealed a deterioration in water quality in the Dnipro-Bug Estuary and the Ingul, Ingulets and Southern Bug rivers. Particularly dangerous levels of pollution were observed in the Inhulets River, where a significant increase in water levels and flooding of civilian infrastructure, residential buildings and households were observed in June 2023. The main reason for the high level of water pollution is sewage, pollution from the destruction of cattle cemeteries, and a large amount of washed-up garbage from flooded areas.
Keywords: surface water pollution; water quality assessment; sanitary and chemical indicators; microbiological indicators